MASALAH-MASALAH YANG DIALAMI SISWA SMP NEGERI 1 KAMPAR TAHUN AJARAN 2015/2016 - Roslawati '; Raja Arlizon; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objectives of this research are 1) to analyze personal problems of male and female students, 2) to analyze emotional problems of male and female students, 3) to analyze learning problems, 4) to analyze family problem of male and female students, 5) to analyze social problems of male and female students, 6) to analyze the problems that experienced by male and female students in general, 7) to analyze the category of the students’ problems in general. The mean of collecting data is questioner. The using of this questioner is in order to obtain data regarding the preference of students’ problems based on personal, emotional, learning, family and social aspects. The subject of this research is all of the students of Junior High School Number 1 Kampar Subdistrict class VII and VIII that consist of 0f 200 students. Sampling is determined by applying total sampling, that all of the population members become the samples. The result shows that male students have more personal problems than female students do, the problem is “ feel being superiors in class “, 2) Male students experienced emotional problems more that female students do, the problem is “ feel nothing problem if their teachers get angry “, 3) Female students experienced learning problems more that male students do, the problem is “ feel afraid of parents’ anger if the get low achievements”, 4) Male students have more family problems than female students do, the problem is “Discussing the problems of children and parents on a certain days”, 5) Male students have more social problem than female students, the problem is “ other students look down upon them “, 6) The general problems experienced by male and female students are personal, emotional and learning problems, 7) In general, the problem that experienced by students is in few category.Keywords: students’ problems